Three-dimensional ultrasonography and power Doppler for discrimination between benign and malignant endometrium in premenopausal women with abnormal uterine bleeding. Issue 1 (December 2016) - El-Sharkawy, Mohamed; El-Mazny, Akmal; Ramadan, Wafaa; Hatem, Dina; Abdel-Hafiz, Aly; Hammam, Mohamed; Nada, Adel
Abstract Background Ultrasonography has been extensively used in women suspected of having a gynecological malignancy. The aim of this study is to evaluate the efficacy of 3D ultrasonography and power Doppler for discrimination between benign and malignant endometrium in premenopausal women with abnormal uterine bleeding. Methods This cross-sectional study included 78 premenopausal women with abnormal uterine bleeding scheduled for hysteroscopy and endometrial curettage. The endometrial thickness (ET), uterine artery pulsatility index (PI) and resistance index (RI), and endometrial volume (EV) and 3D power Doppler vascularization index (VI), flow index (FI), and vascularization flow index (VFI) were measured and compared with hysteroscopic and histopathologic findings. Results The ET (P <0.001), EV (P <0.001), and endometrial VI (P <0.001) and VFI (P  = 0.043) were significantly increased in patients with atypical endometrial hyperplasia and endometrial carcinoma (n  = 10) than those with benign endometrium (n  = 68); whereas, the uterine artery PI and RI and endometrial FI were not significantly different between the two groups. The best marker for discrimination between benign and malignant endometrium was the VI with an area under the ROC curve of 0.88 at a cutoff value of 0.81 %. Conclusion 3D ultrasonography and power Doppler, especially endometrial VI, may be useful for discrimination between benign and malignant endometrium in premenopausal women with abnormal uterine bleeding.